New technological vistas for systems and control the example of wireless networks. - Kumar, P.R.
Over the past four decades, the field of control has woven a rich tapestry of a larger systems theory, with sustained investigations into fundamental issues such as control, estimation, stability, optimality, adaptation, and decentralization. These issues are the fundamental ingredients in many new proposed technologies, which are now within our collective purview. They provide a profusion of practical examples of problems that may have sometimes abstractly engaged our attentions in the past and offer a wealth of opportunities for imaginative solutions. The opportunities are ours to seize. That is the central thesis of this article, and the author uses the example of wireless networking, an area of great interest in the emerging field of information technology, to illustrate it
Keywords: Control systems; Information technology; Network routing; Power control; Quality of service; Systems theory; Wireless networking